2013
DOI: 10.1111/j.1365-2702.2012.04247.x
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s experience of the support from a bereavement follow‐up intervention after the death of a child

Abstract: Aims and objectives. To describe the mothers' experience of the support they received in a bereavement follow-up intervention after the death of a child and their experiences of the intervention programme. The intervention included three complementary components: (1) a support package, (2) peer supporters' contact with mothers and (3) health professionals' contact with mothers. Background. Although several types of intervention have been targeted at grieving parents or mothers, there exists a lack of knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
(129 reference statements)
0
19
0
6
Order By: Relevance
“…Without an existing standard of care, however, follow‐up attempts by a given medical team are inconsistent, and some families are never contacted. A variety of practices are used when there is follow‐up, including making phone calls; sending cards; attending funerals; providing information and resources; connecting parents with other bereaved parents; acknowledging birthdays, holidays, and anniversaries; visiting the family; holding family meetings; and organizing memorial services . Qualitative studies have found that phone calls and family meetings after the child's death are beneficial, helping parents feel like their child is remembered, facilitating meaning‐making, responding to unanswered questions about their child's care, reassuring them they did everything they could, and providing a sense of closure .…”
Section: Resultsmentioning
confidence: 99%
“…Without an existing standard of care, however, follow‐up attempts by a given medical team are inconsistent, and some families are never contacted. A variety of practices are used when there is follow‐up, including making phone calls; sending cards; attending funerals; providing information and resources; connecting parents with other bereaved parents; acknowledging birthdays, holidays, and anniversaries; visiting the family; holding family meetings; and organizing memorial services . Qualitative studies have found that phone calls and family meetings after the child's death are beneficial, helping parents feel like their child is remembered, facilitating meaning‐making, responding to unanswered questions about their child's care, reassuring them they did everything they could, and providing a sense of closure .…”
Section: Resultsmentioning
confidence: 99%
“…(9-14.) Tuen merkitys lapsen kuoleman jälkeisessä tilanteessa on tunnistettu, ja tutkimusta erilaisista tukimuo doista ja niiden vaikuttavuudesta on tehty (13,(15)(16)(17)(18)(19). Myös parisuhdenäkökulma on ollut kes kiössä joissakin tutkimuksissa (3,(6)(7)(8)(20)(21)(22), mutta parisuhteeseen toivottua tukea lapsen kuoleman jälkeisessä elämäntilanteessa ei ole tutkittu, vaikka tiedetään lapsen kuoleman ole van kriisi parisuhteelle (3,6,7).…”
Section: A R T I K K E L Iunclassified
“…Joidenkin näkemysten mukaan kyse ei ole sosiaalisesta tues ta, jos tuen antajana on ammattilainen, yh teisö tai esimerkiksi järjestö (30,32). Toisaalta monissa tutkimuksissa myös ammattilaiset näh dään sosiaalisen tuen antajina (12, 16,35,36), esimerkiksi täydentämässä läheisten antamaa riittämätöntä tukea (34,35). Keskustelua käy dään myös siitä, onko olemassa ammattimainen sosiaalisen tuen muoto (32,34).…”
Section: Tuki Lapsen Kuoleman Jälkeenunclassified
See 1 more Smart Citation
“…Parents report desiring to maintain a relationship with their child's healthcare providers (Nikkola, Kaunonen, & Aho, ; Reilly, Hews, Hastings, & Vaughan, ; Welch et al., ; Woodgate, ). Such actions validate their grief and affirm the parent's sorrow while demonstrating remembrance and honor of the child, all of which are hugely important to the parents.…”
Section: Lessons From Experience: Unspoken Needs Of Bereaved Parentsmentioning
confidence: 99%